Tea Consumption and Risk of Cancer: An Umbrella Review and Meta-Analysis of Observational Studies. Issue 6 (15th July 2020) - Kim, Tai Lim; Jeong, Gwang Hun; Yang, Jae Won; Lee, Keum Hwa; Kronbichler, Andreas; van der Vliet, Hans J; Grosso, Giuseppe; Galvano, Fabio; Aune, Dagfinn; Kim, Jong Yeob; Veronese, Nicola; Stubbs, Brendon; et al.
ABSTRACT: Tea is one of the most widely consumed beverages, but its association with cancer risk remains controversial and unclear. We performed an umbrella review to clarify and determine the associations between tea consumption and various types of cancer by summarizing and recalculating the existing meta-analyses. Meta-analyses of observational studies reporting associations between tea consumption and cancer risk were searched on PubMed and Embase. Associations found to be statistically significant were further classified into levels of evidence (convincing, suggestive, or weak), based on P value, between-study heterogeneity, prediction intervals, and small study effects. Sixty-four observational studies (case-control or cohort) corresponding to 154 effect sizes on the incidence of 25 types of cancer were included. Forty-three (27.9%) results in 15 different types of cancer were statistically significant. When combining all studies on the same type of cancer, 19 results in 11 different types of cancer showed significant associations with lower risk of gastrointestinal tract organ cancer (oral, gastric, colorectal, biliary tract, and liver cancer), breast cancer, and gynecological cancer (endometrial and ovarian cancer) as well as leukemia, lung cancer, and thyroid cancer. Only the reduced risk of oral cancer in tea-consuming populations (OR = 0.62; 95% CI: 0.55, 0.72; P value < 10 −6 ) was supported by convincing evidence. Suggestive evidence was found for 6 results on biliary tract, breast, endometrial, liver, and oral cancer. To summarize, tea consumption was shown to have protective effects on some types of cancer, particularly oral cancer. More well-designed prospective studies are needed with consideration of other factors that can cause biases.